1977
DOI: 10.2466/pms.1977.44.2.527
|View full text |Cite
|
Sign up to set email alerts
|

Time Estimation and Total Subjective Time

Abstract: Techniques for estimation of magnitude were used in a questionnaire given to 100 university students to test the hypothesis that the subjective duration of an interval of actual time decreases in proportion to total subjective time rather than total chronological age. The results supported the subjective time hypothesis for retrospective reports of perceived duration of a year at both one-half and one-quarter of the subject's present age. In both cases the subjective time hypothesis provided a better fit to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0
2

Year Published

1984
1984
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 1 publication
2
22
0
2
Order By: Relevance
“…For Lernlich (1975)) it is subjective time that is sensed, not real time, whereas for Janet (1877), chronological age is the basis for the sense of real time. Lemlich (1975) reported support for his predictions derived from the square-root function, and Walker (1977) confirmed this report.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…For Lernlich (1975)) it is subjective time that is sensed, not real time, whereas for Janet (1877), chronological age is the basis for the sense of real time. Lemlich (1975) reported support for his predictions derived from the square-root function, and Walker (1977) confirmed this report.…”
supporting
confidence: 87%
“…The present study attempts to test the square-root model using the same procedure as was used by Lemlich (1975) and Walker (1977). I n addition, because these measures of rate and duration of time at different ages are purely subjective, a measure of time estimation was also recorded which may be compared to an objective standard.…”
mentioning
confidence: 99%
“…Some evidence supporting this point was presented by Lemlich (1975), who suggested that the subjective duration of a year varies inversely with the square root of the person's age and reported results in line with his hypothesis. Lemlich's results were confirmed in general by Walker (1977) and by Joubert (1983). It might therefore be concluded that some biological clock (or some complex ofinterrelated clocks; Schroots & Birren, 1990) slows progressively as a function of increasing age, thereby giving rise to the subjective feeling that external time is passing ever faster.…”
supporting
confidence: 67%
“…Finally, participants were asked to make a very long-term duration comparison of the present year to a year when they were one-quarter or one-half their current age. Although lacking the rigor and exactitude of short-term duration judgements (seconds to minutes), several researchers have investigated these very long-term retrospective estimates on a time scale of years (Gallant et al, 1991;Lemlich, 1975;Walker, 1977). These types of estimates do not involve an internal clock, but they may involve recall processes that caffeine may affect (Smith et al, 1993).…”
Section: Purpose Of Studymentioning
confidence: 99%